APOPTOSIS INDUCTION OF EPIFRIEDELINOL ON HUMAN CERVICAL CANCER CELL LINE - Yang, Jie; Fa, Jing; Li, Bingxing (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Present investigation evaluates the antitumor activity of epifriedelinol for the management of cervical cancerby inducing process of apoptosis.Methods: Human Cervical Cancer Cell Line, C33A and HeLa were selected for study and treated with epifriedelinol at aconcentration of (50-1000 μg/ml). Cytotoxicity of epifriedelinol was estimated by MTT assay and induction of apoptosiswas assessed by estimating the activity of caspase 3, 8 and 9 enzyme, apoptosis assay and translocation of cytochrome c.Moreover an expression of several proteins that plays role in the apoptosis process was estimated by western blot method.Results: Result of the study suggested that treatment with epifriedelinol significantly decrease the viability count ofcancerous cell in a dose perndent manner and also enhances the formation of oligonucleosome in both the cell lines.However activity of caspase enzymes and translocation of cytochrome c were enhanced after treatment with epifriedelinol.It was also observed that epifriedelinol treatment alters the ratio of pro-apoptotic to anti-apoptotic proteins and enhances theexpressions of inhibitor of apoptosis proteins (IAP).Conclusion: Result of our study proves the anticancer activity of epifriedelinol in cervical cancer by inducing apoptosis astreatment with it enhances the production of oligonucleosomes, translocation of cytochrome c and activity caspaseenzymes.